2011
DOI: 10.1016/j.jmb.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The Energetic Contribution of Induced Electrostatic Asymmetry to DNA Bending by a Site-Specific Protein

Abstract: DNA bending can be promoted by reducing the net negative electrostatic potential around phosphates on one face of the DNA, such that electrostatic repulsion among phosphates on the opposite face drives bending toward the less negative surface. To provide the first assessment of the energetic contribution to DNA bending when electrostatic asymmetry is induced by a site-specific DNA binding protein, we manipulated the electrostatics in the EcoRV endonuclease-DNA complex by mutation of cationic sidechains that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 105 publications
2
20
1
Order By: Relevance
“…2 that the amplitude of the jump in the SH signal increased as the concentration of Mg 2þ increased. Because the SH jump occurs before a significant portion of DNA is cleaved, the Mg 2þ acts at early times as an electrolyte that screens the repulsive interactions between the neighboring phosphate groups (3,(41)(42)(43). It thereby facilitates the binding of EcoR1 to DNA and allows for a more facile bending of DNA at the reaction site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 that the amplitude of the jump in the SH signal increased as the concentration of Mg 2þ increased. Because the SH jump occurs before a significant portion of DNA is cleaved, the Mg 2þ acts at early times as an electrolyte that screens the repulsive interactions between the neighboring phosphate groups (3,(41)(42)(43). It thereby facilitates the binding of EcoR1 to DNA and allows for a more facile bending of DNA at the reaction site.…”
Section: Resultsmentioning
confidence: 99%
“…The total SH intensity, I 2ω ðtotalÞ is the incoherent sum of the contributions made by the individual particles to the SH intensity, where I 2 ωðjÞ is proportional to the absolute square of the second harmonic electric field generated by the microparticle j, i.e., I 2ω ðjÞ ∼ jE 2ω ðjÞj 2 . If the interface is charged, as it is in the experiments described here, largely due to the attachment of DNA molecules to the microparticle surface, then there is an additional source of SH light due to the third-order polarization, P ð3Þ 2ω , of the interfacial species, which is a product of three electric fields given by, P ð3Þ 2ω ¼ χ ð3Þ E ω E ω E static ðrÞ; [3] where E static ðrÞ is the electric field, predominantly due to DNA, at a distance, r, from the microparticle that polarizes the surrounding molecules, and χ ð3Þ is the third-order susceptibility. It is because E static ðrÞ is a zero frequency electric field that the third-order polarization generates light at 2ω.…”
Section: Background: Second Harmonic Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments assessing Cu 2þ enhancement of binding used the same double-strand deoxyoligonucleotide TCGCGAATTCGCG as that in the ESR experiments. Equilibrium association constants (K A ) for wild-type EcoRI and His114Tyr (AECu 2þ ) were measured by the nitrocellulose filter binding assay as described (34,55). For assays in the absence of Cu 2þ , EDTA (1 mM) was included in the binding buffer (30 mM NEM, 10% glycerol, 10% dioxane, 100 μM dithiothreitol, 100 μg∕mL bovine serum albumin) plus 0.3 M KCl; pH 8.0, 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…4A). Divalent metals generally promote protein-DNA binding by decreasing the charge repulsion between the protein and nearby DNA phosphates (15,33,34). For example, we previously showed that the competitive inhibitor Ca 2þ binds to EcoRI at the negative charge cluster in the active site and thereby increases the equilibrium association constant (K A ) as much as 380-fold (15).…”
mentioning
confidence: 99%